Experimental Investigation of the Corrosion Rate of Factory-Original Motorcycle Exhausts in NaCl Solution and Natural Seawater - Fadhilla, Eky Nur; Alva, Sagir (Universitas Mercu Buana, 2025)
Abstract– Corrosion is a significant factor that decreases the performance and service life of motorcycle components, especially exhaust pipes that are directly exposed to the environment. This study aims to analyze and compare the corrosion rate of factory-made motorcycle exhausts when exposed to two corrosive media: a 3.5 wt% sodium chloride (NaCl) solution and natural seawater. An immersion test was conducted under laboratory conditions for seven days (168 h) using eight AISI 1010 coupons (2 × 2 cm). Four specimens were immersed in seawater, and four in 3.5 % NaCl. After pickling, each coupon was weighed, immersed, cleaned, and re-weighed. Mass loss was converted to a corrosion rate using the gravimetric method and expressed in millimeters per year (mm· year¹). The average corrosion rate in seawater was 4,121.9 mm/year, whereas in 3.5% NaCl it was 71.7 mm/year. The significantly higher rate in seawater is attributed to additional ions, such as magnesium, calcium, and sulfate, that accelerate electrochemical reactions. These findings underscore the importance of adequate surface protection for exhaust pipes, particularly for motorcycles operating in coastal or high-humidity environments, and serve as a basis for developing corrosion-resistant materials or coatings for automotive components.